Electroacupuncture Attenuates Neuropathic Pain and Comorbid Negative Behavior: The Involvement of the Dopamine System in the Amygdala - Zhang, Xue-Hui; Feng, Chen-Chen; Pei, Li-Jian; Zhang, Ya-Nan; Chen, Liu; Wei, Xu-Qiang; Zhou, Jia; Yong, Yue; Wang, Ke (Frontiers in Neuroscience, 2021)
Neuropathic pain (NeuP) is an important clinical problem accompanying negative mood symptoms. Neuroinflammation in the amygdala is critically involved in NeuP, and the dopamine (DA) system acts as an important endogenous anti-inflammatory pathway. Electroacupuncture (EA) can improve the clinical outcomes in NeuP, but the underlying mechanisms have not been fully elucidated. This study was designed to assess the effectiveness of EA on pain and pain-related depressive-like and anxiety-like behaviors and explore the role of the DA system in the effects of EA. Male Sprague-Dawley rats were subjected to the chronic constrictive injury (CCI) model to induce NeuP. EA treatment was carried out for 30 min once every other day for 3 weeks. The results showed that CCI caused mechanical hyperalgesia and depressive and anxiety-like behaviors in rats and neuroinflammation in the amygdala, such as an increased protein level of TNFα and IL-1β and activation of astrocytes. EA treatment significantly improved mechanical allodynia and the emotional dysfunction induced by CCI. The effects of EA were accompanied by markedly decreased expression of TNFα, IL-1β, and glial fibrillary acid protein (GFAP) in the amygdala. Moreover, EA treatment reversed CCI-induced down-regulation of DA concentration, tyrosine hydroxylase (TH) expression, and DRD1 and DRD2 receptors. These results suggest that EA-ameliorated NeuP may possibly be associated with the DA system to inhibit the neuroinflammation in the amygdala.